El sistema nacional de salud del Perú. Entrevista al Dr. David Tejada de Rivero - Cañizares Fuentes, Wilson Ricardo (2019)
About my doctoral thesis: “Evolution of the health system of Peru, 2005-2014. Good management practices “, from the Facultad de Medicina, Universidad Nacional Mayor de San Marcos, in 2017, i conducted an in-depth interview with Dr. David Tejada de Rivero in june 2015. On the previous occasion I had already interviewed him Primary Health Care and its role in the Alma Ata declaration, available on YouTube. The thesis sought to understand and explain the advances and challenges of the national health system of Peru, good practices and the factors that influenced its implementation. To achieve this purpose, based on the qualitative research methodology, the opinions, discourse and reflections of senior executives of the Ministry of Health, public health experts, academics and representatives of Peruvian civil society were consulted, including Dr. David Tejada The interview was conducted in his apartment in Miraflores, Lima, recorded and transcribed for further analysis. The interview was previously consulted and agreed upon with the interviewee, as well as all the interviews that were made about the study. Considering the academic and historical interest, the importance of publishing the complete interview of Dr. David Tejada de Rivero as a tribute and recognition of his important contributions to Peruvian and world public health was considered.